난치실모양각막염에서 10% N-acetylcysteine 점안액의 효과 - 임화랑(Hwa Rang Lim), 고재웅(Jae Woong Koh) (Daihan angwa haghoi jabji, 2019)
목적: 난치실모양각막염환자에서 10% N-acetylcysteine 점안액의 효과를 알아보고자 하였다. 대상과 방법: 실모양각막염으로 진단 받은 20명 환자의 29안을 후향적으로 관찰하였다. 실모양각막염의 원인, 치료 방법, 증상의 경감, 실모양체 수, 각막형광염색, 실모양각막염의 관해 정도 및 재발 유무를 조사하였다. 결과: 19안은 실모양체 제거, 치료용 콘택트렌즈, 점안 항생제 및 스테로이드, 0.05% cyclosporine 점안액(Restasis®, Allergan, Irvine, CA, USA), 인공눈물, 눈물점마개 등으로 치료 후 호전을 보였다. 1개월 이상 위의 통상적인 치료에 반응하지 않은 10안에는 10% N-acetylcysteine 점안액을 추가하였다. 7안은 평균 56.22 ± 24.52일에 질병의 완전한 관해를 보였다. 2안은 실모양체가 2개 이하로 남는 부분 관해를 보였으며 나머지 1안은 자극감으로 점안을 중단하였다. 결론: 10% N-acetylcysteine은 기존의 치료에 반응하지 않는 난치실모양각막염에서 효과적인 치료법으로 고려해 볼 수 있겠다. Purpose: To analyze the effects of topical 10% N-acetylcysteine on patients with refractory filamentary keratitis. Methods: The present study included 29 eyes from 20 patients diagnosed with filamentary keratitis. We analyzed the cause of filamentary keratitis, types of treatments, symptom scores, number of filaments, fluorescein staining, degrees of remission, and recurrence of the disease. Results: A total of 19 eyes treated with filament removal, therapeutic contact lenses, topical antibiotics, topical steroids, topical 0.05% cyclosporine, artificial tears, and punctal plugs showed improvements. Topical 10% N-acetylcysteine was added to 10 patients who did not respond to the usual treatment for more than 1 month. Seven eyes showed a complete remission of disease at an average of 56.22 ± 24.52 days. Two eyes showed a partial remission with less than 1-2 fillaments. One eye stopped 10% N-acetylcysteine treatment because of an irritable sensation. Conclusions: Topical 10% N-acetylcysteine was an effective treatment for refractory filamentary keratitis. KCI Citation Count: 0